The Effectiveness of Probing Techniques in Learning Biology on Learning Outcomes and Perceptions in Class IX Students of SMP Negeri 2 Sengkang, Wajo Regency - Najmiah Najmiah; Gunawan Gunawan; Fakhruddin Fakhruddin; Hasmawati Hasmawati; Nurjannah Nurjannah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
Education is not only about the discourse on how to shape young people into competent generations of the nation, but education also includes the practical realm of how the process is applied. The type of research used in this research is experimental research that seeks to find the influence of other variables under tightly controlled conditions. The research method used in this research is quantitative analysis method, namely study that emphasizes its analysis on numerical data or numbers obtained by statistical methods and is carried out in inferential study or the context of hypothesis testing so that the significance of the relationship between the variables studied is obtained. This research is a process that begins with observations in the form of prior experiences on the implementation of learning in class IX.2 SMP Negeri 2 Sengkang, Wajo Regency in the way of preliminary data collection. The results in this study are that students 'perceptions of learning using probing techniques are positive, students feel learning becomes more interesting; students' thinking skills become more trained by answering questions from the teacher. The teacher's perception is excellent about learning using probing techniques; the teacher feels happy to guide students to further improve their thinking skills with questions that are by the level of thinking ability. Reproductive systems learning material in biology learning using probing techniques is more effective than ordinary learning.